The Influence of Sales Training and Sales Experience through Adaptive Selling Behavior on Salesperson Performance - Yuli Hernanto; Nila K. Hidayat; Firdaus Basbeth (Budapest International Research and Critics University, 2022)
The competitive conditions in heavy equipment sales are very dynamic, and assessing the sales force's performance is an essential factor in guiding managerial decisions to improve the efficiency and effectiveness of the sales organization. Sales training must be provided consistently to all salespeople to enhance their competence. Experienced salespeople also play an important position in the business in contributing value to customers and company productivity. This study examines the effect of sales training and sales experience on salesperson performance through adaptive selling behavior. This quantitative research uses primary data; Structural Equation Modeling (SEM) PLS was used to analyze the data obtained from ABC Company. Researchers obtained 96 respondent data based on predetermined criteria, which were analyzed using SmartPLS software. The results showed that the seven hypotheses tested were accepted. Based on the findings of this study that sales training, sales experience, and adaptive selling behavior directly affect salesperson performance; sales training and sales experience directly affect adaptive selling behavior; adaptive selling behavior can also mediate sales training and sales experience affects salesperson performance. This study also shows that sales experience is the most influential variable on adaptive selling behavior, so the management of ABC Company also needs to make strategies and competency acceleration programs that can accelerate sales experience.